2019
DOI: 10.5653/cerm.2019.46.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Does conventional freezing affect sperm DNA fragmentation?

Abstract: Objective: Sperm cryopreservation has been widely used in assisted reproductive technology, as it offers great potential for the treatment of some types of male infertility. However, cryopreservation may result in changes in membrane lipid composition and acrosome status, as well as reductions in sperm motility and viability. This study aimed to evaluate sperm DNA fragmentation damage caused by conventional freezing using the sperm chromatin dispersion test. Methods: In total, 120 fresh human semen samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Despite the extensive progress that has been made in the field, decreases in sperm motility and DNA integrity are commonly observed after cryopreservation 30,39 . In this report we found that rapid freezing using R18S3 + MTG also significantly reduced sperm motility and increased DNA fragmentation in both wildtype and mutant mouse strains, observations consistent with previous results in mice 26,29 and humans [30][31][32]40 . In this report, we also found that DFI of frozen-thawed sperm from mutant mouse strains was consistently and highly correlated with male mouse fertility compared to traditional measures of sperm quality (count, morphology, and motility).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the extensive progress that has been made in the field, decreases in sperm motility and DNA integrity are commonly observed after cryopreservation 30,39 . In this report we found that rapid freezing using R18S3 + MTG also significantly reduced sperm motility and increased DNA fragmentation in both wildtype and mutant mouse strains, observations consistent with previous results in mice 26,29 and humans [30][31][32]40 . In this report, we also found that DFI of frozen-thawed sperm from mutant mouse strains was consistently and highly correlated with male mouse fertility compared to traditional measures of sperm quality (count, morphology, and motility).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased motility is also caused by damage to mitochondria that affects the production of adenosine triphosphate (ATP), which is the energy resource required for sperm to be motile. Decreased sperm motility is caused by mitochondrial damage [22]. Sperm mitochondria are composed of matrix helices located in the middle part (mid-piece).…”
Section: Discussion the Post-freeze Thawing Quality Of Holstein Bull Sperm And The Correlation With Fertility Levelmentioning
confidence: 99%
“…One of the products of lipid peroxidation is MDA [ 6 ]. Free radicals of ROS may cause lipid peroxidation and mitochondrial and nuclear DNA base modifications [ 40 ]. Modification of 8-OH-guanine or 8-OH-20-deoxyguanosine will destabilize the DNA structure and causes SDF [ 8 ].…”
Section: Discussionmentioning
confidence: 99%